T cell specificity and cross reactivity towards enterobacteria, Bacteroides, Bifidobacterium, and antigens from resident intestinal flora in humans. Issue 6 (1st June 1999) - Duchmann, R; May, E; Heike, M; Knolle, P; Neurath, M; zum Büschenfelde, K-H Meyer
Abstract : BACKGROUND: T cell responses to normal intestinal bacteria or their products may be important in the immunopathogenesis of chronic enterocolitis. AIMS: To investigate the T cell specificity and cross reactivity towards intestinal bacteria. PATIENTS/METHODS: T cell clones were isolated with phytohaemagglutinin from peripheral blood and biopsy specimens of inflamed and non-inflamed colon from five patients with inflammatory bowel disease (IBD) and two controls. T cell clones were restimulated with anaerobic Bacteroides and Bifidobacteria species, enterobacteria, and direct isolates of aerobic intestinal flora. T cell phenotype was analysed by single-cell immunocyte assay. RESULTS: Analysis of 96 T cell clones isolated from peripheral blood and biopsy specimens from two patients with IBD showed that both Bifidobacterium and Bacteroides species specifically stimulate proliferation of CD4+TCRαβ+ T cell clones from both sites and that cross reactivity exists between these anaerobic bacteria and different enterobacteria. Analysis of 210 T cell clones isolated from three patients with IBD and two controls showed that indigenous aerobic flora specifically stimulate T cell clones from peripheral blood and biopsy specimens from a foreign subject. Some of these flora specific T cell clones were cross reactive with defined enterobacteria. In addition, T cell clones stimulated by their own indigenous aerobic flora were identified in patients with IBD. CONCLUSION: Immune responses to antigens from the intestinal microflora involve a complex network of T cell specificities.